Postoperative hypothermia following non-cardiac high-risk surgery: A prospective study of temporal patterns and risk factors. - Itajiba Paternosti Sabbag (Public Library of Science (PLoS), 2021)
Background and objectives Hypothermia occurs commonly during surgery and can cause postoperative complications. We aimed to describe the characteristics and outcomes of hypothermia in patients undergoing major surgeries. Methods This prospective, observational, multicenter study of a nationally representative sample included all patients over 18 years of age admitted to an intensive care unit (ICU). Thirty ICUs were selected randomly at national level. The main outcome measure was the proportion of patients who developed postoperative hypothermia in the first 24 hours of ICU admission. Patients were divided into three groups based on temperature: <35°C, <36°C, and ≥36°C (no hypothermia). Patients' characteristics, postoperative complications, and risk factors were evaluated in all groups. To verify whether hypothermia was a strong risk factor for postoperative complications, a Kaplan-Meier curve was generated and adjusted using a Cox regression model. Results In total, 738 patients had their temperatures measured. The percentage of patients with temperature <35°C (median [Q1-Q3], 34.7°C [34.3-34.9°C]) was 19.1% (95% confidence interval [CI] = 16.1-22.5) and that of patients with temperature <36°C (median [Q1-Q3], 35.4°C [35.0-35.8°C]) was 64% (95% CI = 58.3-70.0). The percentage of surgical complications was 38.9%. Patients with hypothermia were older, had undergone abdominal surgeries, had undergone procedures of longer duration, and had more comorbidities. A postoperative temperature ≤35°C was an independent risk for composite postoperative complications (hazard ratio = 1.523, 95% CI = 1.15-2.0), especially coagulation and infection. Conclusions Inadvertent hypothermia was frequent among patients admitted to the ICU and occurred more likely after abdominal surgery, after a long procedure, in elderly patients, and in patients with a higher number of comorbidities. Low postoperative temperature was associated with postoperative complications.